Pendidikan Islam dalam Gerakan Pramuka di Kampus IAIN Palopo - Makmur, Makmur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to examine the implementation of Islamic education in the Scout Movement activities at the IAIN Palopo Campus. Through a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation of Racana Pramuka members, instructors, and extracurricular lecturers. The results of the study indicate that the Scout Movement is a strategic medium in shaping the religious, leadership, and social character of students. Islamic values ​​such as honesty, discipline, responsibility, brotherhood, and religious moderation are integrated through various scouting activities, both in the form of routine training, field activities, and leadership training programs. The Islamic education implemented is holistic and contextual, making Scouting an effective non-formal educational medium in an Islamic college environment. These findings recommend the importance of strengthening synergy between Scout instructors, lecturers, and institutions in designing more adaptive scouting programs based on Islamic values.